(untitled) - Berkenkotter, Carol (Hillsdale, N.J., 1995)
The authors' studies of disciplinary communication examine operations of systems as diverse as peer review in scientific publications and language in a first grade science classroom. The methods used include case study and ethnographic techniques, and rhetorical and discourse analysis
Keywords: Rhetoric,Hùng biện,Discourse analysis